Spatial factors affecting young females’ disaster exposure in municipalities facing population decline - Jun Sakamoto (PLoS ONE, 2025)
Understanding and reducing the risk of natural disasters is crucial for maintaining the economy and society. Since Japan is a disaster-prone country and the most advanced nation in the world regarding aging and population decline, it necessitates a natural disaster risk analysis that considers both challenges. This paper represents the first study to explore the risk of natural disasters, specifically for young females exposed to four types of events: floods, tsunamis, storm surges, and sediment disasters, particularly in municipalities at risk of vanishing. We identified municipalities with a high proportion of young females exposed to these natural disasters and examined them from a geographical perspective. Utilizing a spatial regression model, we statistically analyzed the factors influencing the proportion of the exposed population. The result showed that young females exposed to flooding tend to the areas with a higher proportion of habitable land, inland regions, and locations abundant in rivers and lakes. Conversely, young females affected by tsunamis tend to be in coastal areas with few buildings. Additionally, those exposed to storm surges are often in regions characterized by features such as rice fields and other facilities. In the case of landslides, young females tend to reside in areas where habitable land is scarce, such as coastal regions. Our findings suggest that municipalities with a risk of citywide flooding or storm surge should enhance countermeasures, such as implementing building regulations in high-hazard residential areas. Additionally, it recommends that municipalities with a risk of tsunami or sediment should relocate hazardous housing.